Blood polyphenol concentrations and differentiated thyroid carcinoma in women from the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Zamora-Ros, R; Lujan-Barroso, L; Achaintre, D; Tong, TYN (Oxford University Press, 2020)
Background Polyphenols are natural compounds with anticarcinogenic properties in cellular and animal models, but epidemiological evidence determining the associations of these compounds with thyroid cancer (TC) is lacking.